Red, black or white? - Petru, Simona (Documenta Praehistorica, 2006)
In this paper the use of the pigments in the Paleolithic is presented, and some ideas of the symbolic meaning of colours are suggested. The colour red might have been a symbol of transformation, and as such, it was used in burials and for painting the Venus figurines. In the Slovenian Paleolithic, there is scant evidence of importance of colour and only a few finds of stonesused for the grinding of the red pigment have been found.
Keywords: Slovenia; Slovenija; prazgodovina; arheološke najdbe; paleolitik; barvila; barve; barvanje; simboli; symbol